Faktor-Faktor Yang Mempengaruhi Pemberian Asi Pada Bayi Neonatal Di Rsia Pertiwi Makassar - Aswita Amir; Nursalim Nursalim; Aliffiani Widyansyah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Breast milk contains high immune antibodies and killer germs that can reduce the risk of infant mortality but exclusive breastfeeding coverage in Indonesia is only 55,7% and has not reached the government target of 80%. This study aims to determine the relation between delivery process of baby, breast crawl and mother’s knowledge with exclusive breastfeeding at RSIA Pertiwi Makassar.The research is an analytical research with cross sectional design. Samples of this study are 155 newborn babies at RSIA Pertiwi Makassar. Data collected by interview using questionnaire then analyzed by Chi Square Test in SPSS program. The results show that there are 54,2% respondents who gave exclusive breastfeeding. There are 59,4% respondents with normal delivery process. There are 20,6% respondents who did breast crawl. Thera are 11,6% respondents with good knowledge. The result of statistical test shows that there are relation between delivery process of baby, breast crawl, and mother’s knowledge with exclusive breastfeeding.